Democracy after liberalism : pragmatism and deliberative politics - Talisse, Robert B. (Routledge, 2005)
This book critically evaluates liberalism, the dominant attempt in the tradition of political philosophy to provide a philosophical foundation for democracy and argues for a conception of deliberative democracy to meet this need.